NANOG Reverses the Myogenic Differentiation Potential of Senescent Stem Cells by Restoring ACTIN Filamentous Organization and SRF‐Dependent Gene Expression. (11th July 2016) - Mistriotis, Panagiotis; Bajpai, Vivek K.; Wang, Xiaoyan; Rong, Na; Shahini, Aref; Asmani, Mohammadnabi; Liang, Mao‐Shih; Wang, Jianmin; Lei, Pedro; Liu, Song; Zhao, Ruogang; Andreadis, Stelios T.
Abstract: Cellular senescence as a result of organismal aging or progeroid diseases leads to stem cell pool exhaustion hindering tissue regeneration and contributing to the progression of age related disorders. Here we discovered that ectopic expression of the pluripotent factor NANOG in senescent or progeroid myogenic progenitors reversed cellular aging and restored completely the ability to generate contractile force. To elicit its effects, NANOG enabled reactivation of the ROCK and Transforming Growth Factor (TGF)‐β pathways—both of which were impaired in senescent cells—leading to ACTIN polymerization, MRTF‐A translocation into the nucleus and serum response factor (SRF)‐dependent myogenic gene expression. Collectively our data reveal that cellular senescence can be reversed and provide a novel strategy to regain the lost function of aged stem cells without reprogramming to the pluripotent state. Stem Cells 2017;35:207–221 Abstract : NANOG restores the myogenic and contractile capacity of senescent stem cells and progeria derived myofibroblasts. Hair follicle derived Mesenchymal Stem Cells (MSC) were transduced with a tetracycline regulatable vector that carries the NANOG gene. This system allows NANOG expression only when cells are treated with the tetracycline analog, Doxycycline. Cells were serially passaged until they became senescent (late passage, LP MSC). Subsequently Dox was added to the culture medium to induce NANOG expression in LP MSC (LP NANOG MSC) and the myogenic capacity was evaluated and compared to early passage (EP) MSC. Similar experiments were also performed with myofibroblasts derived from patients with an accelerating aging disease (Hutchinson Gilford Progeria Syndrome (HPGS)). (A‐B): Western Blot for ACTA2 and SRF. (C‐D) SRF dependent transcriptional activity (CArG‐box). (E‐F) Immunocytochemistry for ACTA2. (G‐H): Contractile force using 3D collagen microtissue. (I): Schematic illustration describing the effects of NANOG on senescent cells. GM: Growth Medium, DM: Differentiation Medium. Scale bar: 20 μm for immunocytochemistry and 200 μm for the microtissues, data are presented as mean ± standard deviation, n = 3, *: designates statistical significance as compared to LP, LP DM or HGPS, HGPS DM ( p < .05), #: designates statistical significance as compared to LP NANOG GM or HGPS NANOG GM ( p < .05).